A study of color development from D-psicose and Methionine Maillard Reaction Products (MRPs). Issue 1 (February 2021) - Al-Baarri, A N; Widayat,; Legowo, A M; Ranini, A A; Setyawan, B A; Lestari, F P
Abstract: The effect of heating time on the Maillard reaction between D-psicose and methionine to produce Maillard reaction products (MRPs) was investigated. This research was conducted at 50°C under aseptic condition. Color development was determined using chroma meter to obtain the value of L*, a* and b* every hour for 16 hours. The results showed that the elevation clearly appeared in the last heating process as the color changed of L* value was decreased. As conclusion, the heating process of D-psicose and Methionine provide development on color appearance against time of heating. This result may have benefit in food application as seasoning.